Experimental study and numerical simulation analysis of the fire resistance of high-strength steel columns with rectangular sections under axial compression. (May 2021) - Wu, Yiwen; Fan, Shenggang; He, Bingbing; Li, Chenxu; Zhou, Hang
Abstract: Based on the performance of Q550 (yield strength f y  = 550 MPa) high-strength steel, mechanical property tests at room temperature and elevated temperatures were first carried out. Second, fire tests were carried out on 8 unconstrained Q550 high-strength steel columns with rectangular sections under axial compression. The mechanical properties and failure modes of high-strength steel columns under fire exposure were revealed. Finally, ABAQUS finite element software was used to establish a refined finite element model of high-strength steel columns, and numerical simulation analysis was carried out to analyse the influence of various parameters on the fire resistance. The results show that (1) the critical temperature and the maximum axial displacement of the steel columns decrease with increasing load ratio n . (2) the smaller the slenderness ratio λ is, the smaller the maximum axial displacement, while the critical temperature changes slightly. (3) there are two failure modes of the specimens: overall buckling and overall and local coupling buckling. (4) the thermal mechanical coupling analysis method can effectively simulate the behaviour of high-strength steel columns under fire exposure. The research in this paper establishes a theoretical foundation for the improvement of the fire resistance design method of high-strength steel columns. Highlights: The key influence factor on the fire resistance of high-strength columns is load ratio. There are two failure modes of the test specimens: overall buckling and overall and local coupling buckling. The fire resistance of columns can be simulated by the thermal mechanical coupling analysis method.